A risk table to address concerns external to stock assessments when developing fisheries harvest recommendations - Martin W. Dorn (Taylor & Francis Group, 2020)
This paper develops a risk table to facilitate incorporation of additional information into the fisheries stock assessment and management process. The risk table is designed to evaluate unanticipated ecosystem and environmental impacts on marine resources that may require a rapid management response. The risk table is a standardized framework to document concerns about the assessment model, population dynamics, and the ecosystem/environment that are not explicitly addressed within the stock assessment model. A scoring procedure is used to evaluate the severity of the concern. These concerns can then be evaluated in support for or against a reduction from the maximum Acceptable Biological Catch while providing reviewers and stakeholders transparent documentation of the concerns. The risk table was applied successfully to several stocks on a trial basis during the 2018 groundfish assessment cycle for the North Pacific Fishery Management Council, and will be used for all full groundfish assessments in 2019. Rapid changes in climate are likely for Alaska marine ecosystems in coming decades, and these changes are not entirely predicable. Therefore, we avocate that the risk table approach should be included in the suite of management tools used to address the effects of climate change on Alaska marine resources.